A Slotted Microstrip Antenna with Fractal Design for Surveillance Based Radar Applications in X- Band - Kumar Dhakad, Shailendra; Dwivedi, Umesh; Rawat, Sanyog; Agarwal, Yash; Joshi, Anay (International Journal of Engineering and Technology, 2018)
This paper proposes a unique micro-strip patch antenna which has a hexagonal fractal pattern which can mainly be used for ground based surveillance radar applications. To further optimize the functioning of the antenna, multiple slots have been added to the ground plane, and a stepped pattern has been implemented to increase the current density and the gain. A detailed study of the stages of development of the antenna has been made, illustrating the effect that various design elements have on the operating characteristics of the final design. There is specific emphasis on the use of slots in the ground plane. Variations in return loss, gain, VSWR, operating frequency and bandwidth with changes in the design of the ground plane have been documented. The antenna is designed to perform in the X-band, more specifically around 9 GHz, making it well suited for short range search. The final iteration of the antenna design, including various stages of slotting in the ground plane, works at 8.7 GHz, which is well within the X-band range, and has a return loss of around 30 dB.Â Â